Perancangan Website Bisnis Pada Siswa Madrasah Di Kabupaten Majene, Sulawesi Barat - Nur Fitriayu Mandasari; Muhammad Ashdaq; Valentino Aris (Lembaga Penelitian Pengabdian kepada Masyarakat, 2023)
This activity aims to improve the abilities of students at MAN 1 Majene, West Sulawesi so that they can have digital capabilities in facing current world developments. The problem faced by Man 1 Majene students is the lack of ability to participate and follow developments in the digital world, especially the use of digital platforms for economic activities. After participating in this activity, MAN Majene students are expected to have the skills to create a simple business website that can be used to support family business activities. The subjects of this activity are students (i) of MAN 1 Majene which is located in Majene Regency, West Sulawesi Province. The number of participants was 20 people from various departments at Madrasah schools. Training activities were carried out for one day using mentoring, lectures, questions and answers and practice methods. Training results: (1) Student(i) has the ability to design a simple business website, (2) Student(i) has an understanding of digital marketing techniques, (3) Student(i) has the technical ability to optimize websites organically.